Lipoprotein (A), Homocysteine, Lipid Profile With Oxidative Stress In Nephrotic Syndrome And Cardiovascular Nephropathy. - JYOTI DWIVEDI; PURNIMA DEY SARKAR (International Journal of Pharma and Bio Sciences, 2010)
Lipoprotein (a) and homocysteine are important markers for oxidative stress in nephrotic syndrome and cardiovascular nephropathy. The purpose of this study was to examine selected markers of oxidative stress and antioxidant defense in nephrotic syndrome & cardiovascular nephropathies. Therefore, this study was carried out to investigate oxidant and antioxidant status in nephrotic syndrome and cardiovascular patients with nephritis. The blood samples were analyzed for quantitation of malondialdehyde as index of lipid peroxide, vitamin C, total antioxidant capacity, lipoprotein (a), homocysteine & lipid profile. Significantly increased levels of serum total cholesterol, low density lipoprotein, malondialdehyde, homocysteine, lipoprotein (a) (p<0.001) and decreased levels of serum high density lipoprotein, total antioxidant capacity, total protein, albumin, & plasma vitamin C (p<0.001) were noticed in the patients with cardiovascular nephropathy as compared to nephrotic syndrome and control subjects. In conclusion the oxidative stress is increased in nephrotic syndrome & cardiovascular nephropathic patients due to hyperhomocysteinemia, hyperlipoproteinemia and hypoproteinemia. Cardiovascular nephropathy patients had more oxidative stress than nephrotic syndrome patients.